PENGARUH GAYA KEPEMIMPINAN DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PADA PT NUSALIMA DIGDAYA NUSANTARA DI JAKARTA TIMUR - Asrul Sani; Aden Prawiro Sudarso (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
performance at PT Nusalima Digdaya Nusantara. The research employed a quantitative approach, with data collected through questionnaires distributed to 56 respondents. Data analysis was conducted using simple and multiple linear regression to test the research hypotheses. The results show that leadership style (X1) has a positive and significant effect on employee performance (Y), as indicated by a t-value of  3.580 > t-table 1.290 and a significance level of 0.000 > 0.05. Meanwhile, work ethic (X2) has a positive and significant effect on employee performance, with a t-value of 11.482 > t-table 1.290 and a significance level of 0.000 < 0.05. Simultaneously, leadership style and work ethic have a positive and significant effect on employee performance, as indicated by an F-value of 64.706 > F-table 3.09 and a significance level of 0.000 < 0.05. In conclusion, employee performance at PT Nusalima Digdaya Nusantara can be improved by strengthening work ethic while continuously developing effective leadership practices.